Problem Mindfullness Perspektif Worldview Islam - Jarman Arroisi; Maulana Dzunnurrain (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2023)
Mindfulness has recently become a mainstay for the treatment of various modern mental illnesses. However, Islam sees this as problematic regarding the objective of surrendering oneself and concentrating one's thoughts. This research aims to examine the concept of mindfulness from an Islamic worldview perspective. This research uses descriptive analytical methods. Data is processed using content analysis. The results of this study show several important points. First, the practice of mindfulness has a theological-historical connection, namely in the form of activities inherited from Buddhist believers known as sati. Second, the Islamic worldview considers that all activities are a form of commitment and have a vertical relationship to the creator Allah SWT. which has ta'abbudiyyah values ​​and this requires involvement in activities with religious values. Third, in Islamic literature, mental problems are important and their treatment has special emphasis. Fourth, the soul has a vertical bond to the Creator so that treatment of the soul must be fundamental and comprehensive. With that, tazkiyah al-nafs in Islamic teachings is the best solution in eliminating mental illnesses such as stress, skinophrezia, etc. by living the Islamic Worldview, bringing Islamic treasures to life, and providing fundamental solutions to every problem in life.